Kei Traditional Marriages within Indonesia’s Legal Framework - Jeujanan, Grasela Natalia; Toatubun, Hamza (Jurnal Ilmu Hukum Kyadiren, 2023)
This study examines the implementation of traditional Kei marriages in Indonesia and their interaction with the national legal system. The research employs a sociological juridical approach, utilizing library studies, structured interviews, and questionnaires for data collection. Kei traditional marriages, characterized by elaborate processions and rituals, reflect deeply-rooted cultural values such as reverence for ancestors, unity, and mutual cooperation. The patrilineal structure of Kei marriages aligns with recognized forms of customary marriage in Indonesia. Despite their distinctiveness, Kei marriages fundamentally uphold principles enshrined in national marriage law, including mutual consent and community involvement. The concept of pela gandong adds a unique dimension, emphasizing broader social cohesion. While Kei marriages effectively incorporate elements mandated by national law, ongoing dialogue is essential to address potential conflicts with evolving universal values like gender equality. This study demonstrates how indigenous traditions can enrich Indonesia’s cultural heritage while reinforcing the national legal framework, providing deeper context to the institution of marriage.